Q1) If \(cos(x-y)+cos(y-z)+cos(z-x)=\frac{-3}{2}\) and \(cosx+cosy+cosz=a\) and \(sinx+siny+sinz=b\). Find \(a\) and \(b\)

Q2) Two non-conducting infinite wires have shapes as shown above. The linear charge densities of wire (1) and wire (2) are

\(x\quad if\quad x\leq -a~ and~ x\geq a\\ \\ 0\quad if\quad -a<x<a)\)

and

\(y\quad if\quad y\leq -a~ and~ y\geq a\\ \\ 0\quad if\quad -a<y<a)\)

respectively where \((x,y)\) are coordinates of points on the wire. An electron is released from origin, the unit vector along the direction of velocity of the electron just after its release will be in terms of \(\hat { i } \) and \(\hat { j } \)

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewest\( cosx + cosy + cosz = a \)

\( \cos^2x + \cos^2y + \cos^2z + 2\cos x\cos y + 2\cos y\cos z + 2 \cos x\cos y = a^2\)

Likewise, \( \sin^2x + \sin^2y + \sin^2z + 2\sin x\sin y + 2\sin y\sin z + 2 \sin x\sin y = b^2\)

Adding, \( \cos^2x + \cos^2y + \cos^2z + 2\cos x\cos y + 2\cos y\cos z + 2 \cos x\cos y + \)

\( \sin^2x + \sin^2y + \sin^2z + 2\sin x\sin y + 2\sin y\sin z + 2 \sin x\sin y = a^2 + b^2 \)

\( \implies 1 + 1 + 1 + 2(\cos x\cos y + \cos y\cos z + \cos x\cos y + \sin x\sin y + \sin y\sin z + \sin x\sin y) = a^2 + b^2 \)

\( \implies 3 + 2(\cos(x-y) + \cos(y-z) + \cos(z-x)) = a^2 + b^2 \)

\( \implies 3 + 2* \frac{-3}{2} = a^2 + b^2 \)

\( 0 = a^2 + b^2 \implies a = 0\quad \& \quad b = 0 \)

Log in to reply

Thanks for this man.

Log in to reply

@Raghav Vaidyanathan @Ronak Agarwal @Mvs Saketh

Log in to reply

The answer to q 1 is very easy: \(a=b=0\).

Log in to reply

Ans 2 q2 seems to be zero too.

Log in to reply

can u explain in brief the first part

Log in to reply

Log in to reply